PERANCANGAN SISTEM DETEKSI TINGGI PERMUKAAN AIR DITANGKI DITAMPILKAN PADA LCD DAN LAMPU INDIKATOR BERBASIS NODEMCU ESP8266 - Siringoringo, Cindy Elisa Pitaloka; Siringo-ringo, Kolombus; Hutabarat, Marvin F. S. (LPPM ISTP, 2024)
A tool has been designed that can detect low, medium and full water levels. The series of tools designed is based on the NodeMCU ESP8266 microcontroller as the CPU. Because the water level detection tool still uses the Atmel, Atmega, Arduino Uno family microcontrollers as the CPU. The tool is designed to use a magnetic switch water sensor module as a water level detector, a NodeMCU ESP8226 microcontroller as a CPU, an LCD as a low, medium and full information display, a buzzer as an alarm sound signal generator indicating that the water is full, an LED indicator as an indication of the water level level. low, medium, and full. The designed tool can detect the height of the water level in the embankment. The LCD displays low information if buoy water sensor 1 is submerged in water, buoy water sensors 2 and 3 have not been submerged in water. The LCD displays information if the buoy water sensors 1 and 2 are submerged in water, the buoy water sensor 3 has not been submerged in water. The LCD displays full information when the float water sensors 1, 2, and 3 are submerged in water.